Pre-clinical evaluation of a divalent liposomal vaccine to control invasive candidiasis - Augusto Costa-Barbosa; Maria Inês Pacheco; Andreia C. Gomes; Tony Collins; Manuel Vilanova; Célia Pais; Alexandra Correia; Paula Sampaio (npj Vaccines)
Abstract Candida albicans causes systemic infections with 20–50% mortality in critically ill and immunocompromised patients, despite antifungal treatment. Current therapies face limitations, including toxicity and resistance, underscoring the need for prophylactic vaccines. This study presents a novel divalent liposomal vaccine, delivering C. albicans Cht3 and Sap2 antigens. Vaccination induced protective Th1/Th17 immunity, a balanced Th1/Th2 ratio, antigen-specific antibodies, and boosted macrophage activity, improving survival in a mouse model of invasive candidiasis.